2006
DOI: 10.1111/j.1551-2916.2006.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Grain Growth in Barium Titanate Doped with Alumina

Abstract: The effect of additions of ≤1 mol% Al2O3 on abnormal grain growth in BaTiO3 sintered for periods of ≤60 min at 1350°C has been studied. Addition of ≤0.2 mol% Al2O3 caused an increase in the nucleation and growth rates of abnormal grains, with further additions causing a decrease. This behavior is explained by interface‐controlled growth. Dopant adsorption reduces both the edge free energy and the step velocity of a grain, causing the nucleation and growth rates of abnormal grains to increase, pass through a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 57 publications
(144 reference statements)
0
14
0
Order By: Relevance
“…8,23,25 Fig. 3 shows TEM micrographs of undoped (0T), 0.7 mol% TiO 2 -doped (0.7T), and 1.5 mol% TiO 2 -doped NBT-5BT (1.5T) samples sintered at 1200 • C for 1 h. As the crystal structure of NBT-5BT is pseudo-cubic (rhombohedral with a = b = c = 3.8864Å and α = β = γ = 89.2 • ), 28,29 the selected area diffraction patterns in the insets of the figure indicate that the crystallographic planes of the three different grains have (0 0 1) orientation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…8,23,25 Fig. 3 shows TEM micrographs of undoped (0T), 0.7 mol% TiO 2 -doped (0.7T), and 1.5 mol% TiO 2 -doped NBT-5BT (1.5T) samples sintered at 1200 • C for 1 h. As the crystal structure of NBT-5BT is pseudo-cubic (rhombohedral with a = b = c = 3.8864Å and α = β = γ = 89.2 • ), 28,29 the selected area diffraction patterns in the insets of the figure indicate that the crystallographic planes of the three different grains have (0 0 1) orientation.…”
Section: Resultsmentioning
confidence: 98%
“…Some experimental studies have shown that the grain coarsening behavior was abnormal and normal for faceted and rounded grains, respectively, in the same system by changing temperature, 14,24 adding dopants, 7,8,11,17,25 or varying oxygen partial pressure. 8,26,27 Cho et al 14 studied the effect of temperature on grain shape and grain coarsening behavior in the NbC-Co system.…”
Section: Introductionmentioning
confidence: 98%
“…This may be due to the broader grain size distribution of these samples, as in the case of BaTiO 3 doped with Al 2 O 3 . 43 In a sample with a bimodal grain distribution,r may be determined by the grains in the first peak, as these are dissolving. 44 The grains in the second peak then may have a large enough driving force to continue growing.…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed in several systems including BaTiO 3 24 Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 , 25 and columbite structured ceramics. 26 Fisher et al 24 suggested that the development of very large grains was encouraged by the faceting of interfaces between adjacent grains, and that the presence of a liquid phase would reduce the critical driving force required for abnormal grain growth.…”
Section: Microstructurementioning
confidence: 99%